Experimental Equipment to Develop Teaching of the Concept Viscosity - Modesto Pérez-Sánchez; Ruzan Galstyan-Sargsyan; M. Isabel Pérez-Sánchez; P. Amparo López-Jiménez (MDPI AG, 2018)
Some of the subjects have complex concepts, which are currently taught using deductive methods in the first years of University Degree. However, the experience shows the results obtained from students’ learning goals were quite low. Therefore, the use of inductive method is a crucial factor to improve students’ learning results and re-thinking the way to teach in basic subject of Engineering Bachelor Degree. One example is the subject called Fluid Mechanics, which is present in many Bachelor Degrees. This matter has abstract concepts, which are normally taught by traditional methods. This type of teaching makes difficult to be understood by the student. This research proposes an inductive methodology to work the viscosity concept using an activity. In this test, the student has to carry out some measurements with different fluids using a simple measurement device while they participated actively in the learning.